Émergence insoumise: réflexions sur la persistance du racisme systémique envers les femmes autochtones - Wylde, Cyndy (Hannenorak, 2024)
« Émergence insoumise s'ouvre sur un souvenir de l'autrice qui attend un taxi après un colloque : « Non, mais croyez-vous vraiment que moi, une femme des Premières Nations, je vais aller attendre seule le soir, à Val-d'Or? » Ces mots, adressés au gardien qui lui indique que les portes de l'université sont sur le point de fermer, seront le catalyseur d'une réflexion sur le sort réservé aux femmes autochtones, aussi bien dans le milieu carcéral que dans la société canadienne en général. Alternant entre les réminiscences personnelles et les analyses du racisme systémique afin d'aller au-delà des statistiques et des préjugés, cet essai de Cyndy Wylde s'inscrit dans une tradition de littérature de combat, qui bouscule les idées reçues et dynamite le confort et l'indifférence. »
Keywords: 2000 à aujourd'hui; amérique du nord; amériques; approches et analyses; canada; corps; cours; discipline; discours dominant; féminisme autochtone; phi4336; philosophie; premier cycle; privilèges; périodes historiques; québec; racisme; racisme systémique; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences

#MeToo and testimonial injustice: An investigation of moral and conceptual knowledge - Hänel, Hilkje C (Philosophy & Social Criticism, 2022)
Two decades ago, Tarana Burke started using the phrase ‘me too’ to release victims of sexual abuse and rape from their shame and to empower girls from minority communities. In 2017, actress Alyssa Milano made the hashtag #MeToo go viral. This article’s concern is with the role of testimonial practices in the context of sexual violence. While many feminists have claimed that the word of those who claim to being sexually violated by others (should) have political and/or epistemic priority, others have failed to recognize the harm and injury of instances of sexual violence that are not yet acknowledged as such and failed to listen to victims from marginalized social groups. In fact, some feminists have attacked #MeToo for mingling accounts of ‘proper’ sexual violence and accounts that are not ‘proper’ experiences of sexual violence. My aim in this article is to show why this critique is problematic and find a philosophically fruitful way to understand the #MeToo-movement as a movement that strives for moral and conceptual progress.
Keywords: #metoo; approches et analyses; cours; cycles supérieurs; discipline; fem9000; justice sociale; patriarcat; philosophie; racisme; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; violences sexistes et sexuelles; violences sexuelles

Le contrat sexuel - Pateman, Carole (La Découverte, 2022)
« Par quel étrange paradoxe le contrat social, censé instituer la liberté et l'égalité civiles, a-t-il maintenu les femmes dans un état de subordination ? Pourquoi, dans le nouvel ordre social, celles-ci n'ont-elles pas accédé, en même temps que les hommes, à la condition d'« individus » émancipés ? Les théories du contrat social, héritées de Locke et de Rousseau, et renouvelées depuis Rawls, ne peuvent ignorer les enjeux de justice que soulève le genre. Carole Pateman montre, dans cet ouvrage désormais classique, que le passage de l'ordre ancien du statut à une société moderne du contrat ne marque en rien la ﬁn du patriarcat. La philosophe met ainsi au jour l'envers refoulé du contrat social : le « contrat sexuel », qui, via le partage entre sphère privée et sphère publique, fonde la liberté des hommes sur la domination des femmes. Il s'agit là moins d'exploitation que de subordination, comme le démontre l'autrice en analysant le contrat de mariage, mais aussi l'ensemble des contrats touchant à la propriété de la personne, de la prostitution à la maternité de substitution, jusqu'à l'esclavage et au salariat. Ainsi s'engage, à partir du féminisme, une critique de la philosophie politique libérale dans son principe même : pour Carole Pateman, un ordre social libre ne peut en aucun cas être de type contractuel. »– Quatrième de couverture.
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; citoyenneté; contrat social; cours; discipline; droits des femmes*; fem1000; histoire et politique; incontournable; justice sociale; outils; ouvrages de références; patriarcat; phi4336; philosophie; philosophie politique; pol4212; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; science politique; science politique et droit; sciences humaines; systèmes d'oppressions; thématiques; théories féministes; violences; états-unis

Contesting Islam, constructing race and sexuality: The inordinate desire of the West - Thobani, Sunera (Bloomsbury Academic, 2022)
Les affrontements politiques actuels de la « guerre contre le terrorisme » illustrent que l'interaction au sein et entre les civilisations dites occidentales et moyen-orientales est en constante évolution. Un thème récurrent est cependant la façon dont l'Islam et les musulman.e.s signifient « l'Ennemi » dans l'imaginaire socioculturel occidental et sont devenu.e.s « l'Autre » contre lequel l'Occident s'identifie. Dans un mélange unique et perspicace de théorie raciale critique, féministe et postcoloniale, Sunera Thobani examine comment l'islam est à la base de la formation de l'identité occidentale à des moments critiques de son histoire, y compris les croisades, la Reconquista et la période coloniale. Plus précisément, elle explore comment la masculinité et la féminité se forment à ces moments charnières et quel rôle le féminisme a joué dans les guerres contre l'islam « radical ». En exposant ces relations symbiotiques, Thobani explore comment le retour de la « religion » retravaille les politiques raciales, de genre et sexuelles par lesquelles la société occidentale se définit, et plus spécifiquement, se définit contre l'islam. Contester l'islam, construire la race et la sexualité déballe les orthodoxies conventionnelles et non conventionnelles pour ouvrir de nouveaux espaces dans la façon dont nous pensons à l'identité sexuelle et raciale en Occident et au rôle crucial que l'islam a eu et continue d'avoir dans son développement.
Keywords: antiracisme; approches et analyses; cours; discipline; fem3400; histoire et politique; personnes musulmanes; philosophie; premier cycle; racisme; sciences humaines; sexisme; sexualité; système colonial; systèmes d'oppressions; thématiques; violences

Hermeneutical Backlash: Trans Youth Panics as Epistemic Injustice - George, B. R.; Goguen, Stacey (Feminist Philosophy Quarterly, 2021)
In this paper we use the contemporary example of trans youth panics to introduce the notion of hermeneutical backlash, in which defenders of an established, unjust hermeneutical regime actively work to undermine and discredit hermeneutical liberation. We argue that the strategies and tropes of the trans youth panic illustrate a general propaganda vulnerability of epistemic liberation movements (including familiar examples from recent history), and so are troubling for reasons that go beyond their application to trans youth. This exploration of a few specific cases of hermeneutical liberation and hermeneutical backlash calls attention to the need for further theoretical work on the dynamics of struggles for (and against) hermeneutical justice.
Keywords: approches et analyses; backlash herméneutique; cours; cycles supérieurs; discipline; discours dominant; discours médiatique; enfants trans*; fem9000; histoire et politique; hétérosexisme; injustices herméneutiques; militance; philosophie; philosophie féministe; sciences humaines; systèmes d'oppressions; thématiques; transphobie; violences

Applied epistemology - Lackey, Jennifer (Oxford University Press, 2021)
Leading philosophers bring the tools of contemporary epistemology to bear on some of the most pressing social and political questions facing us as agents in the world today. This volume explores a diverse range of topics as they relate to epistemology under broad themes including injustice, race, feminism, sexual consent, and the internet.
Le texte d' Emmalon Davis, “A Tale of Two Injustices: Epistemic Injustice in Philosophy” a été donné au cours FEM9000.
Keywords: approches et analyses; corps; cours; cycles supérieurs; discipline; fem9000; histoire et politique; injustice; justice sociale; philosophie; sciences humaines; thématiques; violences; épistémologie; éthique

Elsa DORLIN - Se défendre - Une philosophie de la violence - UPOP Marseille (2020)
Se défendre. Une philosophie de la violence Conférence d’Elsa DORLIN En 1685, le Code noir défendait « aux esclaves de porter aucune arme offensive ni de gros bâtons » sous peine de fouet. Au XIXe siècle, en Algérie, l’État colonial interdisait les armes aux indigènes, tout en accordant aux colons le droit de s’armer. Aujourd’hui, certaines vies comptent si peu que l’on peut tirer dans le dos d’un adolescent noir au prétexte qu’il était « menaçant ». Une ligne de partage oppose historiquement les corps « dignes d’être défendus » à ceux qui, désarmés ou rendus indéfendables, sont laissés sans défense. Ce « désarmement » organisé des subalternes pose directement, pour tout élan de libération, la question du recours à la violence pour sa propre défense. Des résistances esclaves au ju-jitsu des suffragistes, de l’insurrection du ghetto de Varsovie aux Black Panthers ou aux patrouilles queer, Elsa Dorlin retrace une généalogie de l’autodéfense politique. Sous l’histoire officielle de la légitime défense affleurent des « éthiques martiales de soi », pratiques ensevelies où le fait de se défendre en attaquant apparaît comme la condition de possibilité de sa survie comme de son devenir politique. Cette histoire de la violence éclaire la définition même de la subjectivité moderne, telle qu’elle est pensée dans et par les politiques de sécurité contemporaines, et implique une relecture critique de la philosophie politique, où Hobbes et Locke côtoient Frantz Fanon, Michel Foucault, Malcolm X, June Jordan ou Judith Butler.
Keywords: antiracisme; approches et analyses; cours; discipline; militance; patriarcat; philosophie; pol5480; premier cycle; racisme; ressource en ligne; sciences humaines; système colonial; systèmes d'oppressions; thématiques; violences

Metaepistemic Injustice and Intellectual Disability: a Pluralist Account of Epistemic Agency - Catala, Amandine (Ethical Theory and Moral Practice, 2020)
The literature on epistemic injustice currently displays a logocentric or propositional bias that excludes people with intellectual disabilities from the scope of epistemic agency and the demands of epistemic justice. This paper develops an account of epistemic agency and injustice that is inclusive of both people with and people without intellectual disabilities. I begin by specifying the hitherto undertheorized notion of epistemic agency. I develop a broader, pluralist account of epistemic agency, which relies on a conception of knowledge that accounts not only for propositional knowing, but also for other types of knowing that have been largely neglected in debates on epistemic injustice and agency. Based on this pluralist account of epistemic agency, I then show that people with intellectual disabilities qualify as epistemic agents and therefore as subjects of epistemic justice. Finally, I argue that this pluralist account of epistemic agency pushes us to revisit the current conception of epistemic injustice and to expand its taxonomy in two important ways.
Keywords: EDI; agentivité épistémique; approches et analyses; capacitisme; cours; cycles supérieurs; discipline; fem9000; handicap intellectuel; injustices épistémiques; inégalités; justice sociale; justice épistémique; philosophie; savoir propositionnel; sciences humaines; systèmes d'oppressions; taxonomie des savoirs; thématiques; violences; éthique

Microaggressions and philosophy - Freeman, Lauren; Weekes Schroer, Jeanine (Routledge, 2020)
"This is one of the first books to offer a comprehensive philosophical treatment of microaggressions. Its aims are to provide an intersectional analysis of microaggressions that cuts across multiple groups and dimensions of oppression and marginalization, and to engage a variety of perspectives that have been sidelined within the discipline of philosophy. The volume gathers a diverse group of contributors: philosophers of color, philosophers with disabilities, philosophers of various nationalities and ethnicities, and philosophers of several genders and gender identities. Their unique frames of analysis articulate both how the concept of microaggressions can be used to clarify and sharpen our understanding of subtler aspects of oppression and how analysis, expansion, and reconceiving the notion of a microaggression can deepen and extend its explanatory power. The essays in the volume are divided into four thematic parts. The essays in Part I seek to defend microaggressions from common critiques and to explain their impact beyond the context of college students. In Part II the contributors set forth a framework for legitimizing microaggressions research that takes into account issues of measurement, scale, and replication. Part III explores the harms of microaggressions. The chapters show how small slights can accumulate to produce significant harm at the macro level, demonstrate how microaggressions contribute to epistemic harm, and establish novel understandings of racial and accent-triggered microaggressions. Finally, Part IV addresses issues of disability and ableism within the context of microaggressions. It includes commentary on transgender athletes, disciplinary techniques for bodily nonconformity, ableist exceptionalism, and deafness. Microaggressions and Philosophy features cutting-edge research on an important topic that will appeal to a wide range of students and scholars across disciplines. It includes perspectives from philosophy of psychology, empirically informed philosophy, feminist philosophy, critical race theory, disability theory, philosophy of language, philosophy of science, and social and political philosophy"– Provided by publisher.
Keywords: EDI; approches et analyses; capacitisme; cours; cycles supérieurs; discipline; fem9000; histoire et politique; hétérosexisme; intersectionnalité; inégalités; micro-agression; philosophie; psychologie; racisme; sciences humaines; sexisme; sofia; systèmes d'oppressions; thématiques; transphobie; violences; études critiques de la race; études critiques du handicap

Epistemic Decolonization as Overcoming the Hermeneutical Injustice of Eurocentrism - Posholi, Lerato (Philosophical Papers, 2020)
This paper is broadly concerned with the question of what epistemic decolonization might involve. It is divided into two parts. The first part begins by explaining the specifically epistemic problem to which calls for epistemic decolonization respond. I suggest that calls for decolonization are motivated by a perceived epistemic crisis consisting in the inadequacy of the dominant Eurocentric paradigm to properly theorize our modern world. I then discuss two general proposals, radical and moderate, for what epistemic decolonization might involve. In the second part, I argue that the inadequacy of Eurocentric epistemic resources constitutes a hermeneutical injustice caused by an irreducible form of epistemic oppression. I then argue that addressing this form of epistemic oppression requires thinking ‘outside’ of the Eurocentric paradigm because the paradigm might fail to reveal and address the epistemic oppression sustaining it. This lends further plausibility to the radical proposal that epistemic decolonization must involve thinking from ‘outside’ the Eurocentric paradigm, but also accommodates the moderate proposal that adopting critical perspectives on Eurocentric thought is an important part of epistemic decolonization.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; discours dominant; décolonisation épistémique; fem9000; féminisme décolonial; injustices herméneutiques; injustices épistémiques; philosophie; sciences humaines; système colonial; systèmes d'oppressions; thématiques; violences; études décoloniales